# The solution to the equation "-5 squared + 25" is 50.

It looks like there might be a typographical error in your equation. If you intended to write "-5 squared + 25," then it would be written as (-5)^2 + 25.

(-5)^2 means -5 raised to the power of 2, which is equivalent to (-5) multiplied by itself: (-5) × (-5) = 25.

Therefore, the equation becomes:

(-5)^2 + 25 = 25 + 25 = 50.

# The solution to the equation "-5 squared + 25" is 50.

Certainly! To solve the expression (-5)^2 + 25 step by step, follow these calculations:

1. **Evaluate (-5)^2:**

$$(-5)^2 = (-5) \times (-5) = 25$$

2. **Add 25 to the result:**

$$25 + 25 = 50$$

Therefore, the step-by-step breakdown of (-5)^2 + 25 is as follows:

$$(-5)^2 + 25 = 25 + 25 = 50$$

Hence, the final solution is 50.

# The conclusion is that the expression (-5)^2 + 25 simplifies to the value of 50.

The step-by-step process involves first squaring -5, which equals 25, and then adding 25 to that result, which gives the final answer of 50.